The intellectual pursuits and oriental attachments of the poet Goethe/ কবিকূলগুরু গ্যোয়েথের জ্ঞানচর্চা ও প্রাচ্যীয় অনুষঙ্গ (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2025)
Goethe, the great poet has been a father figure in German literature as well as world literature. His literary and life practice was too colorful to imitate. Along with his literary pursuits, he also intensively studied a particular sphere of science - Morphology. A distinguished German literary movement was also coined by him. A famous oriental work - Shakuntala changes the philosophical outlook of such renowned writer. Beside the enthusiastic praise of Shakuntala, the influence of Shakuntala and other oriental literary gems on his creation of immortal literature could not be avoided. The less familiar and hidden facts of Goethe’s life and literary practice navigated in this small piece of writings.
Keywords: Abhijñāna- śakuntalā; world literature; Faust; Sturm und Drang; Tragedy; spiritually; Prologue